REEMERGENCE OF RACIAL STEREOTYPE AND DISCRIMINATION IN JORDAN PEELE’S GET OUT (2017) - Atinia Hidayah (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2019)
Racial stereotype has been discussed for many years and its issue is still shown today through various ways including a film. This paper discusses one main problem related to racial issues which is the reemergence of black stereotype in Jordan Peele’s Get Out (2017). This research applied deconstruction approach by Jacques Derrida. The main data were collected from movie’s subtitle and supporting data were taken from books, journals, and other sources that are related to the issue being chosen. The analysis is presented through binary opposition that leads to the deconstruction of the data found. Thus, the finding states that black stereotype is presented through white’s treatment toward black people based on the recollection of black history, their stereotyped behavior and physical discrimination.